Russian-Ukrainian Invasion Through Geopolitical - Riska Saleh; Hendra Maujana Saragih; Andi Dwi Cahya Karuniawan (Dauliyah: Journal of Islam and International Affairs, 2024)
Russia invaded Ukraine because the geopolitical location owned by Ukraine is very strategic to expand influence into Eastern Europe. One factor that makes Ukraine a strategic geopolitical location is that Ukraine can join the North Atlantic Treaty Organization (NATO). If it joins NATO, the NATO treaty states that if there is an attack on one or more NATO countries, it will be considered to be attacking all countries that are members of NATO. NATO members to date number 30 countries, including France, Germany, Italy, the United Kingdom, and the United States. However, to date and shortly, Ukraine is unlikely to join NATO yet. This fact is being used by Russia to invade Ukraine. Russia considers the invasion of Ukraine to be a form of guarding national security. The geopolitical tensions between Russia and Ukraine affect oil prices. This is because Russia is one of the largest oil exporters in the world and a member of OPEC+. This increase in oil prices exacerbates the inflation problems that are being experienced by countries in the world, especially developed countries such as the United States, The United Kingdom, and the European Union. Keywords: Economic Impact, Geopolitics, Invasion, NATO, Russian-Ukraine.